Thinking Outside the Box from The Perspective of a Malaysian School Administrator During A Pandemic as A New Educational Form - Nazeri Mohammad; Arshad Jais (Indonesian Journal of Educational Research and Technology, 2023)
The purpose of this study was to describe Out of the Box from Malaysian School Administrators’ Perspective During Pandemic. We did a literature review to explain this matter. We believe that this study can be used as a reference for the education perspective.